2009
DOI: 10.1186/1742-4933-6-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing on CMV-specific CD8 T cells from CMV seropositive healthy donors

Abstract: Background: Ageing is associated with changes in the immune system with substantial alterations in Tlymphocyte subsets. Cytomegalovirus (CMV) is one of the factors that affect functionality of T cells and the differentiation and large expansions of CMV pp65-specific T cells have been associated with impaired responses to other immune challenges. Moreover, the presence of clonal expansions of CMV-specific T cells may shrink the available repertoire for other antigens and contribute to the increased incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 64 publications
(71 reference statements)
4
55
1
Order By: Relevance
“…This observation is consistent with previous observations showing decreased INFγ secretion in the PBMCs in elderly individuals (Olive et al 2001;Sester et al 2002). CMV-specific CD8 + T cells are increased in old individuals (65-101 years), but not in middle-aged/elderly (41-64 years) individuals, based on staining with HLA-A2 CMV pp65 pentamers (Pita-Lopez et al 2009). Another report demonstrated similar levels of EBV-and CMV-specific CD8 + T cells between young (young 20-61) and old (75-82 years) individuals, identified through HLA-A2 tetramers to EBV BMLF1 and CMV pp65 epitopes, respectively (Colonna-Romano et al 2007;Vescovini et al 2014).…”
Section: Cd8supporting
confidence: 82%
“…This observation is consistent with previous observations showing decreased INFγ secretion in the PBMCs in elderly individuals (Olive et al 2001;Sester et al 2002). CMV-specific CD8 + T cells are increased in old individuals (65-101 years), but not in middle-aged/elderly (41-64 years) individuals, based on staining with HLA-A2 CMV pp65 pentamers (Pita-Lopez et al 2009). Another report demonstrated similar levels of EBV-and CMV-specific CD8 + T cells between young (young 20-61) and old (75-82 years) individuals, identified through HLA-A2 tetramers to EBV BMLF1 and CMV pp65 epitopes, respectively (Colonna-Romano et al 2007;Vescovini et al 2014).…”
Section: Cd8supporting
confidence: 82%
“…It might be interesting to know whether these cells are a by product of timeenduring stimulation by an unknown, infectious agent. One possible candidate would be CMV, since Chidrawar et al (2009) have demonstrated that CMV infection in the elderly influences not only T lymphocytes (Pita-Lopez et al 2009;Pawelec et al 2009Pawelec et al , 2010, but also negatively affects B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant age‐related change in the human immune system is the quality and phenotype of the cytotoxic CD8 T‐cell subset. Indeed, with age, and in chronic infections such as human immunodeficiency virus (Appay et al ., 2007) and cytomegalovirus (Pita‐Lopez et al ., 2009), the majority of CD8 + T cells become antigen‐experienced and acquire a deregulated, pro‐inflammatory phenotype. These late‐differentiated CD8 + T cells possess many features of replicative senescence that have been characterized in long‐term in vitro cultures (Signer et al ., 2008).…”
Section: Cellular Senescence and Immune Cell Fate Decisionmentioning
confidence: 99%